The effectiveness of different dosages of Lime, Alum and Bentonite to improve peat water quality - Situngkir, Devi Yanti; Budijono, Budijono; M. Hasbi, M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract The quality of peat water in general is relatively low and it is needed to be treated by using a coagulation system. Mixture of lime, alum and bentonite might be used as coagulant agents. This study aims to determine the effectiveness of different dosages of lime, alum and bentonite in improving the quality of peat water. Peat water samples were obtained from the Kualu Nenas Village, Kampar, Riau. The was CRD method applied and data were analyzed using Analysis of Variance (ANOVA) with SPSS version 17.0 software. If there is a significant effect, a Duncan's Multiple Range Test 5% level of (DMRT) is applied. There were 4 treatments and 3 replications applied namely P1 (0.50 g lime + 1.36 g alum + 0.34 g bentonite), P2 (0.50 g lime + 1.02 g alum + 0.68 g bentonite), P3 (0.50 g lime + 0.68 g alum + 1.02 g bentonite), P4 (0.50 g lime+ 0.34 g alum + 1.36 g bentonite). In each treatment, a liter of peat water was treated with the mixture for 20 minutes. From these results it can be concluded that a mixture of lime, alum and bentonite can improve the quality of peat water. The best treatment was provided by P2 and the result was pH 7.3, color 32.6 Pt/Co, turbidity 2.10 NTU and organic 37.9 mg / L.Keyword : Alum, Coagulation, Floculation, Turbidity, Organic matters